High-purity carbon quantum dot material and method for preparing the same

The method of dissolving soluble carbon-containing organic matter in ultrapure water and processing under supercritical conditions addresses the limitations of existing carbon quantum dot production methods, achieving high-purity and high-yield carbon quantum dots suitable for industrial production.

JP2025066640AActive Publication Date: 2025-04-23WAJIN CAPITAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024140671
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-04-23
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

Current methods for preparing carbon quantum dots are limited by high facility costs, low yields, and the need for intense reaction conditions, making them unsuitable for large-scale industrial production.

Method used

A method involving the dissolution of soluble carbon-containing organic matter in ultrapure water, followed by processing in a pressure reactor under supercritical conditions (380°C, 23MPa) with cooling and purification using acetonitrile to achieve high-purity carbon quantum dots.

Benefits of technology

This method enables the production of high-purity carbon quantum dots with high yield and consistency, adjustable size and functional groups, and efficient purification, making it suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066640000001_ABST
    Figure 2025066640000001_ABST
Patent Text Reader

Abstract

To provide a method for preparing high-purity carbon quantum dots.SOLUTION: A method includes the steps of: dissolving a soluble carbon-containing organic compound in ultrapure water, filling a pressure reactor with the reaction solution until it is full, and sealing the reactor; starting a heating program, and rapidly raising the temperature to 380°C to maintain the pressure inside the reactor at 23 MPa or higher; starting a cooling system to cool the reaction products inside the reactor; collecting and quantifying the aqueous solution of carbon quantum dots obtained after cooling; and separating and purifying the aqueous solution of carbon quantum dots.SELECTED DRAWING: Figure 8
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of carbon nanomaterials and quantum dots, and in particular to an industrially tunable method for the preparation of high purity carbon quantum dots. [Background technology]

[0002] Carbon quantum dots are usually composed of sp2 / sp3 carbon cores and outer layers containing functional groups such as oxygen / nitrogen, and are monodisperse carbon nanomaterials with sizes of 10 nm or less. They have excellent properties similar to those of conventional semiconductor quantum dots, but can effectively overcome the drawback of poor biocompatibility. They are an ideal alternative to conventional semiconductor materials because of their wide supply source, ease of synthesis and simple functionalization.

[0003] Carbon quantum dots are carbon-based zero-dimensional materials. Carbon quantum dots have many advantages, such as excellent optical properties, good water solubility, environmental friendliness, wide source of raw materials, low cost, and excellent biocompatibility. Since the discovery of carbon quantum dots, many synthesis methods have been developed, including arc discharge, laser pinning, electrochemical synthesis, chemical oxidation, combustion, subcritical hydrothermal synthesis, microwave synthesis, and template methods. Carbon quantum dots have good application prospects in many fields, such as medical imaging technology, environmental monitoring, chemical analysis, catalyst preparation, and energy development.

[0004] However, each of these methods has its own advantages and disadvantages. For example, the chemical vapor deposition method can prepare carbon quantum dots with high crystallinity, but the equipment costs are high and the yield is low, while the electrochemical method has a high yield but the preparation conditions are strict and parameters such as the electrode gap need to be controlled. These methods can prepare various carbon quantum dots, but the reaction processes all involve severe reaction conditions such as high temperature and high pressure, and often involve the generation of many by-products. Therefore, how to efficiently separate and purify the carbon quantum dots produced from the reaction solution is an issue that needs to be solved as soon as possible. At present, the mainstream purification method is to dialyze the aqueous solution of carbon quantum dots and retain the high molecular weight carbon quantum dots to achieve the purpose of separation and purification. However, this method requires a long purification cycle, and the purified product is an aqueous solution of quantum dots. In order to obtain the pure carbon quantum dot product, it is necessary to further separate the carbon quantum dots and water. Some literature mentions that the purification is performed using ethanol centrifugation, but this method requires the use of a large amount of ethanol, and most of the product is lost during the separation process, the purification efficiency is low, and the two-phase liquid is difficult to separate even when centrifuged. In summary, the above two methods are currently limited to use in laboratories and cannot be put into large-scale industrial production. Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by the present invention is to provide a high-purity carbon quantum dot material and a method for preparing the same. [Means for solving the problem]

[0006] In order to solve the above technical problems, the method for preparing high purity carbon quantum dots of the present invention includes: Step 1: dissolving the soluble carbon-containing organic matter in ultrapure water, so that the mass ratio of carbon element in the soluble carbon-containing organic matter to water is 1:10000 to 1:100; Step 2: Filling the pressure reactor with reaction liquid to capacity and sealing the reactor; Step 3: Start the heating program to rapidly increase the temperature to 380°C and maintain the pressure in the reactor at 23 MPa or higher; Step 4: Activating the cooling system to cool the reactants in the reactor; Step 5: After cooling, collecting and quantifying the resulting aqueous solution of carbon quantum dots; Step 6: Separating and purifying the aqueous solution of carbon quantum dots.

[0007] Supercritical water has very active chemistry and interacts with carbonaceous organic matter containing functional groups that are soluble under supercritical conditions, causing the water molecules to interact and react with the functional groups.

[0008] Unlike hydrothermal synthesis, which is commonly used to prepare nanoparticles of metals and inorganic nonmetals, the main driving force is the difference in solubility between soluble precursors or intermediates and the final product, i.e., the reaction proceeds in the direction of decreasing Gibbs free energy. Water exists only as a medium, and its grain growth follows crystallization kinetics, and the grain size is adjusted by controlling temperature, pressure, and reaction time. The difference between the preparation of carbon quantum dots by supercritical water and hydrothermal synthesis is that water participates as a reactant, the mechanism of producing quantum dots is a chemical reaction of organic matter, which does not follow the laws of crystallization kinetics, the products at different stages are different substances, and organic matter is carbonized under supercritical conditions for a long time.

[0009] As a further improvement, after step 1, a soluble dopant material is added to the solution and completely dissolved, the soluble dopant material is an element containing nitrogen, phosphorus or sulfur, and the ratio of the dopant element to the carbon source in the soluble dopant material is less than or equal to 1:1.

[0010] Carbon quantum dots synthesized using only a carbon source and supercritical water have low stability, so dopants containing elements such as nitrogen, phosphorus, and sulfur must be added to stabilize the structure of the carbon quantum dots and adjust the carbon ring structure and functional groups. The soluble carbon source is a soluble organic substance containing 6 or more carbon atoms in the molecule. The soluble dopant material is dimethylsulfoxide.

[0011] Preferably, the reaction time is 10 to 15 minutes in step 3. Water in a supercritical state is very reactive, and if the reaction continues for a long period of time, the organic matter will be carbonized.

[0012] Preferably, the soluble carbon-containing organic matter is an organic molecule such as an organic acid or a sugar, which has high solubility and a rich number of functional groups, resulting in a fast reaction rate and a high quantum dot yield.

[0013] Preferably, the soluble organic acid is one of citric acid, salicylic acid, glutamic acid, and tartaric acid. Preferably, the soluble sugar is any one of glucose, glyceraldehyde, and arabinose. Preferably, the reaction temperature is 380°C.

[0014] Preferably, the cooling time after the reaction is 15 minutes or less. Then, the material is rapidly cooled to room temperature within 15 minutes because the carbon quantum dots are highly active and natural cooling can cause side reactions, leading to the formation of larger organic particles and a lower yield of quantum dots.

[0015] In step 4, the temperature of the reactor is reduced using ethylene glycol coolant at -5°C. This cooling method is more effective, has a faster cooling rate, and is more uniform in cooling rate.

[0016] Preferably, in step 4, the temperature of the reactor is reduced using a glycol coolant at -5°C. The reaction product is cooled using ethylene glycol coolant at -5°C, which can greatly reduce the occurrence of other reactions during natural cooling and improve the yield of quantum dots.

[0017] As a further improvement, step 5 further comprises: 6.1: Add acetonitrile to the solution and shake to mix thoroughly. As a further improvement, the volume ratio of acetonitrile to the carbon quantum dot aqueous solution is 5:1; 6.2: Allowing the mixed solution to stand in the dispenser for 30 minutes; 6.3: The bottom black viscous liquid is collected and dried to remove traces of residual acetonitrile to obtain the pure product of carbon quantum dots.

[0018] Carbon quantum dots have very low solubility in acetonitrile, but acetonitrile has high solubility for impurities that occur during the synthesis of carbon quantum dots. Acetonitrile has a stronger bond with water molecules than carbon quantum dots, and it will take away the water molecules that are bound to the carbon quantum dots. Therefore, when an organic solvent is added to an aqueous solution of carbon quantum dots, acetonitrile will take away the water molecules that are bound to the carbon quantum dots, and as a result, there will be a shortage of water molecules that can bind to the carbon quantum dots, and they will precipitate out of the solution. A small amount of impurities generated simultaneously during the synthesis process cannot precipitate out due to their small content, and will remain in the solution, achieving the purpose of separation and purification.

[0019] As a further improvement, in step 6.3, after collecting the bottom layer of black viscous liquid, add acetonitrile to the black viscous liquid in a 1:1 ratio, shake to mix thoroughly, separate the layers, and then dispense again. Repeat the above steps five times until the volume of the bottom layer of black viscous liquid remains unchanged. After collecting the black viscous liquid and drying to remove traces of residual acetonitrile, a pure product of carbon quantum dots is obtained.

[0020] The present invention claims to protect the carbon quantum dot material prepared by the above carbon quantum dot preparation method. Effect of the Invention

[0021] Compared with the prior art, the method of the present invention for preparing carbon quantum dots using supercritical water has the following beneficial technical effects:

[0022] (1) A wide range of ingredients is available. (2) The preparation process is simple; (3) High yield and consistency; (4) The size and functional groups of carbon quantum dots can be tailored as desired; (5) High refining efficiency and low product loss rate; (6) It is easy to scale up industrially.

[0023] The above description is only an outline of the technical solution of the present invention. In order to make the technical means of the present application more clearly understood and implemented in accordance with the content of the specification, and to make the above and other objectives, features and advantages of the present application more clear and easy to understand, the following detailed description will be given in conjunction with the preferred embodiments of the present application and the accompanying drawings.

[0024] These and other objects, advantages and features of the present application can be better understood by those skilled in the art from the following detailed description of specific embodiments of the present application, taken in conjunction with the accompanying drawings. [Brief description of the drawings]

[0025] In order to more clearly describe the technical solutions in the embodiments of the present application or the prior art, the accompanying drawings which need to be used in the description of the embodiments or the prior art are briefly described below.

[0026] [Figure 1] 1 is a TEM photograph of carbon quantum dots of about 8.5 nm prepared in Example 1. [Diagram 2] 1 is a fluorescence excitation spectrum of the carbon quantum dots prepared in Example 1. [Diagram 3] 1 is an image of yellow fluorescence of the carbon quantum dots prepared in Example 1 under the action of ultraviolet light. [Figure 4] 1 is a TEM photograph of carbon quantum dots of about 2 nm prepared in Example 2. [Diagram 5] 1 is a fluorescence excitation spectrum of the carbon quantum dots prepared in Example 2. [Figure 6]1 is an image of blue fluorescence of the carbon quantum dots prepared in Example 2 under the action of ultraviolet light. [Figure 7] FIG. 13 shows the formation of larger carbon quantum dots after natural cooling. [Figure 8] FIG. 1 shows that the sizes of carbon quantum dots are nearly uniform after cooling to room temperature for 15 minutes. [Figure 8a] FIG. 9 is a partially enlarged view of FIG. 8. [Figure 9] FIG. 1 shows the effect of cooling rate on quantum dot yield. [Figure 10] FIG. 1 shows the effect of reaction time on quantum dot yield. [Figure 11] FIG. 1 is a diagram showing a comparison of the stability of urea and metaphosphoric acid between dimethyl sulfoxide doping and the control group. [Figure 12] FIG. 1 shows the carbonization of sucrose after reacting for 20 minutes under supercritical water conditions. [Figure 13] 13 is a photograph showing dispensing of different ratios of acetonitrile and quantum dot solutions. [Figure 14] Photographs showing different ratios of concentrate and acetonitrile dispensed after repurification. [Figure 15] 1 is a photograph showing the state of layer separation when different solvents are selected. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] In order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions of the embodiments of the present application are clearly and completely described hereinafter in conjunction with the accompanying drawings of the embodiments of the present application.

[0028] The method for producing high purity carbon quantum dots of the present invention includes the following steps: Step 1: Dissolve the soluble carbon-containing organic matter in ultrapure water, and set the mass ratio of carbon element in the soluble carbon-containing organic matter to water to 1:10000 to 1:100; Step 2: Fill the pressure reactor with the reaction solution until it is full and seal the reactor. Step 3: Start the heating program, rapidly increase the temperature to 380°C, and maintain the pressure in the reactor at 23 MPa or higher. Step 4: Activate the cooling system to cool the reactants in the reactor; Step 5: After cooling, the resulting aqueous solution of carbon quantum dots is collected and quantified; Step 6: Separate and purify the aqueous solution of carbon quantum dots.

[0029] Supercritical water has very active chemistry and interacts with carbonaceous organic matter containing functional groups that are soluble under supercritical conditions, causing the water molecules to interact and react with the functional groups.

[0030] Unlike hydrothermal synthesis, which is commonly used to prepare nanoparticles of metals and inorganic nonmetals, the main driving force is the difference in solubility between soluble precursors or intermediates and the final product, i.e., the reaction proceeds in the direction of decreasing Gibbs free energy. Water exists only as a medium, and its grain growth follows crystallization kinetics, and the grain size is adjusted by controlling temperature, pressure, and reaction time. The difference between the preparation of carbon quantum dots by supercritical water and hydrothermal synthesis is that water participates as a reactant, the mechanism of producing quantum dots is a chemical reaction of organic matter, which does not follow the laws of crystallization kinetics, the products at different stages are different substances, and organic matter is carbonized under supercritical conditions for a long time. As a further improvement, after step 1, a soluble dopant material is added to the solution and completely dissolved, the soluble dopant material is an element containing nitrogen, phosphorus or sulfur, and the ratio of the dopant element to the carbon source in the soluble dopant material is less than or equal to 1:1.

[0031] Carbon quantum dots synthesized using only a carbon source and supercritical water have low stability, so dopants containing elements such as nitrogen, phosphorus, and sulfur must be added to stabilize the structure of the carbon quantum dots and adjust the carbon ring structure and functional groups.

[0032] The soluble carbon source is a soluble organic substance containing 6 or more carbon atoms in the molecule. Preferably, the soluble dopant material is an alcohol amine, an amide, a metaphosphoric acid, or dimethylsulfoxide.

[0033] Preferably, the soluble alcohol amine is one of monoethanolamine, diethanolamine, and ethylenediamine;

[0034] Preferably, the soluble amide is one of acetamide, acrylamide, and carbomite.

[0035] As the soluble dopant material, dimethylsulfoxide is most preferably selected. Preferably, the reaction time is 10 to 15 minutes in step 3. Water in a supercritical state is very reactive, and if the reaction continues for a long period of time, the organic matter will be carbonized.

[0036] Preferably, the soluble carbon-containing organic matter is an organic molecule such as an organic acid or a sugar, which has high solubility and a rich number of functional groups, resulting in a fast reaction rate and a high quantum dot yield.

[0037] Preferably, the soluble organic acid is one of citric acid, salicylic acid, glutamic acid, and tartaric acid. Preferably, the soluble sugar is any one of glucose, glyceraldehyde, and arabinose.

[0038] Preferably, the pressure in the reactor is 23 Mpa. Preferably, the reaction temperature is 380°C. Preferably, the cooling time after the reaction is 15 minutes or less.

[0039] Then, the material is rapidly cooled to room temperature within 15 minutes because the carbon quantum dots are highly active and natural cooling can cause side reactions, leading to the formation of larger organic particles and a lower yield of quantum dots.

[0040] In step 4, the temperature of the reactor is reduced using ethylene glycol coolant at -5°C. This cooling method is more effective, has a faster cooling rate, and is more uniform in cooling rate.

[0041] Preferably, in step 4, the temperature of the reactor is reduced using a glycol coolant at -5°C. The reaction product is cooled using ethylene glycol coolant at -5°C, which can greatly reduce the occurrence of other reactions during natural cooling and improve the yield of quantum dots.

[0042] As a further improvement, step 5 further comprises: 6.1: Add acetonitrile to the solution and shake to mix thoroughly. As a further improvement, the volume ratio of acetonitrile to the carbon quantum dot aqueous solution is 5:1; 6.2: Allowing the mixed solution to stand in the dispenser for 30 minutes; 6.3: The bottom black viscous liquid is collected and dried to remove traces of residual acetonitrile to obtain the pure product of carbon quantum dots.

[0043] Carbon quantum dots have very low solubility in acetonitrile, but acetonitrile has high solubility for impurities that occur during the synthesis of carbon quantum dots. The binding ability of organic solvents and water molecules is stronger than that of carbon quantum dots, so when an organic solvent is added to an aqueous solution of carbon quantum dots, the organic solvent takes away the water molecules that are bound to the carbon quantum dots, and as a result, there are not enough water molecules to bind to the carbon quantum dots, so they precipitate out of the solution.

[0044] As a further improvement, in step 6.3, after collecting the lower layer black viscous liquid, add acetonitrile to the black viscous liquid in a ratio of 1:1, shake to mix thoroughly, separate into layers, and dispense again, and repeat the above steps five times until the volume of the lower layer black viscous liquid does not change. That is, it is preferable to perform the step of "after collecting the lower layer black viscous liquid, add acetonitrile to the black viscous liquid in a ratio of 1:1, shake to mix thoroughly, separate into layers, and dispense again" six times. Finally, the black viscous liquid is collected and dried to remove traces of residual acetonitrile, and then a pure product of carbon quantum dots is obtained.

[0045] Example 1 The specific steps are as follows:

[0046] 1) Take 1L of pure water, 100g of citric acid, and 40g of monoethanolamine, mix well to completely dissolve, 2) Pour this solution into a 1 L reactor, 3) Heat the solution to about 380°C, adjust the pressure to 23Mpa or more, and hold for 6 minutes; 4) Activate the cooling system and cool to room temperature at atmospheric pressure for 15 minutes. Then open the reactor and take out the reaction liquid into a dispenser. 5) Add 5 L of acetonitrile to the dispenser, shake thoroughly to mix, and let stand for 30 minutes. 6) Collect the lower layer of black viscous liquid, measure the volume, add acetonitrile in a 1:1 ratio, shake to mix thoroughly, separate the layers, and then dispense again. 7) The lower layer of the black viscous liquid is collected again, and the above steps are repeated five times, at which time the volume of the lower layer of the black viscous liquid remains unchanged, and the total amount of acetonitrile administered is 6 L; 8) Collect the black viscous liquid at the bottom, place it in a vacuum drying oven, and dry it at room temperature for 24 hours to obtain a yellow carbon quantum dot pure product with a wavelength of about 8.5 nm and an emission wavelength of 550 nm.

[0047] Figure 1 is a TEM photograph of carbon quantum dots of about 8.5 nm prepared in Example 1. Figure 1 shows a number of carbon quantum dots with a particle size distribution of 7 to 10 nm. FIG. 2 is the fluorescence excitation spectrum of the carbon quantum dots prepared in Example 1. Figure 3 is a photograph of the yellow fluorescence under the action of ultraviolet light of the carbon quantum dots prepared in Example 1. Figure 3 proves that the carbon quantum dots provided in this example have good fluorescent properties.

[0048] Figures 1 to 3 show a number of carbon quantum dots, which prove that the carbon quantum dots provided by this embodiment have good fluorescent properties, and prove that the method of the present invention can prepare suitable carbon quantum dots.

[0049] Example 2 The specific steps are as follows: 1) Take 1L of pure water, 90g of glucose, and 30g of dimethyl sulfoxide, mix well to dissolve completely, 2) Pour this solution into a 1 L reactor, 3) Heat the solution to about 380°C, adjust the pressure to 23Mpa or more, and hold for 10 minutes; 4) Activate the cooling device and cool to room temperature and atmospheric pressure for 12 minutes, then transfer the reaction liquid to a dispenser. 5) Add 5 L of acetonitrile to the dispenser, shake thoroughly to mix, and let stand for 30 minutes. 6) Collect the lower layer of black viscous liquid, measure the volume, add acetonitrile in a 1:1 ratio, shake to mix thoroughly, separate the layers, and then dispense again. 7) Collect the lower layer of black viscous liquid again, and repeat the above steps until the volume of the lower layer of black viscous liquid does not change, and at this time, the total amount of acetonitrile is 6 L; 8) Collect the black viscous liquid at the bottom, place it in a vacuum drying oven, and dry it at room temperature for 24 hours to obtain blue carbon quantum dots with a diameter of about 2 nm and an emission wavelength of about 450 nm.

[0050] Figure 4 is a TEM image of the approximately 2 nm carbon quantum dots prepared in Example 2. Figure 4 shows a number of carbon quantum dots having a particle size distribution of approximately 2 nm. FIG. 5 is the fluorescence excitation spectrum of the carbon quantum dots prepared in Example 2.

[0051] Figure 6 is a photograph of blue fluorescence under the action of ultraviolet light of the carbon quantum dots prepared in Example 2. Figure 6 proves that the carbon quantum dots provided in this example have good fluorescent performance.

[0052] Figures 4 to 6 show a number of carbon quantum dots, which prove that the carbon quantum dots provided by this embodiment have good fluorescent properties, and prove that the method of the present invention can prepare suitable carbon quantum dots.

[0053] Example 3 1) Take 1L of pure water, 90g of glucose, 10g of ethylenediamine, and 5g of metaphosphoric acid, mix well to dissolve completely, 2) Pour this solution into a 1 L reactor, 3) Heat the solution to about 380°C, adjust the pressure to 23Mpa or more, and hold for 10 minutes; 4) Activate the cooling device, cool to room temperature at atmospheric pressure for 12 minutes, and transfer the reaction liquid to a dispenser. 5) Add 5 L of acetonitrile to the dispenser, shake thoroughly to mix, and let stand for 30 minutes. 6) Collect the lower layer of black viscous liquid, measure the volume, add acetonitrile in a 1:1 ratio, shake to mix thoroughly, separate the layers, and then dispense again. 7) Collect the lower layer of black viscous liquid again, and repeat the above steps until the volume of the lower layer of black viscous liquid does not change, and at this time, the total amount of acetonitrile is 6 L; 8) Collect the black viscous liquid at the bottom, place it in a vacuum drying oven, and dry it at room temperature for 24 hours to obtain blue carbon quantum dots with a diameter of about 2 nm and an emission wavelength of about 450 nm.

[0054] In the method of the present invention, the cooling time after the reaction is preferably within 15 minutes. After the reaction, the cooling system is started and the reactor temperature is reduced to room temperature within 15 minutes using -5°C glycol coolant. This is because carbon quantum dots are highly active, and natural cooling will cause side reactions, leading to the formation of larger organic particles and a reduced yield of quantum dots. In this system, the cooling method is more effective, the cooling rate is faster, and the cooling rate is more uniform because of the use of -5°C glycol coolant.

[0055] The present inventors conducted a comparative experiment to compare the effects of natural cooling and the rapid cooling of the present invention. Figure 7 is a TEM photo of natural cooling, which shows that large carbon quantum dots were generated after cooling, which reduced the yield of quantum dots. Figure 8 is a TEM photo of cooling to room temperature for 15 minutes, which shows that after lowering the temperature, the sizes of the carbon quantum dots are almost the same, and relatively good monodispersity is achieved.

[0056] In the method of the present invention, the preferred reaction time is 10-15 minutes, and the inventors conducted a series of comparative experiments to test the effect of different reaction times on the yield. The reaction times were selected as 5 minutes, 10 minutes, 12 minutes, 15 minutes, and 17 minutes, respectively. As can be seen from Figure 10, the effect is particularly significant when the reaction time is 10-15 minutes. This is believed to be because supercritical water is very active and organic matter is carbonized when reacted for a long time. In Figure 12, sucrose was carbonized after reacting for 20 minutes under supercritical water conditions.

[0057] In the method of the present invention, the soluble dopant material is preferably an alcohol amine, an amide, metaphosphoric acid, or dimethyl sulfoxide. More preferably, the soluble alcohol amine is one of monoethanolamine, diethanolamine, and ethylenediamine, and preferably, the soluble amide is one of acetamide, acrylamide, and carbomite.

[0058] FIG. 11 shows a comparison of the stability of dimethyl sulfoxide doped with urea and metaphosphoric acid as controls. As can be seen from FIG. 11, the effect of dimethyl sulfoxide is better.

[0059] In the present invention, the proportion of acetonitrile in the first purification step was optimized, and the experiments were as follows:

[0060] Add 20mL of carbon quantum dot aqueous solution stock solution to the dispensing funnel, and add acetonitrile in the amount of 20mL to 120mL in sequence at intervals of stock solution:acetonitrile volume ratio of 1:1 to 1:6. As shown in the figure, when the volume ratio is 1:2, the solution first shows obvious layer separation, then the volume of acetonitrile gradually increases, reaching a maximum at 1:5, and then an obvious limit effect begins to appear. When acetonitrile is added again to a volume ratio of 1:6, there is no obvious change from the case of 1:5, so the amount of acetonitrile added during the initial purification is determined to be stock solution:acetonitrile = 1:5. Figure 13 shows the dispensing photos of different ratios of acetonitrile and quantum dot solution.

[0061] Experiment to determine the proportion of acetonitrile in the subsequent purification steps: The lower layer of carbon quantum dot concentrate from the first separation was collected and quantified, and 20 mL of the original solution was purified for the first time to obtain 2 mL of concentrate, which was then placed in a dispensing funnel. 2 mL to 6 mL of acetonitrile were added to the dispensing funnel in sequence at intervals of 1:1 to 1:3 volume ratios of concentrate to acetonitrile. As shown in the figure, after the first addition at a ratio of 1:1, there was no obvious change when acetonitrile was added again, indicating that the limit effect was obvious thereafter. Therefore, the amount of acetonitrile added in subsequent purifications was determined to be concentrate:acetonitrile = 1:1. Figure 14 is a photograph of the case where the ratio of concentrate and acetonitrile was changed when repurifying.

[0062] Experimental validation of purification reagent selection: According to the mechanism of the purification process, the organic reagent used in the purification process must have strong binding force with water and can be mutually dissolved with water in any ratio. Several organic reagents commonly used in laboratories that meet the conditions, such as ethanol, acetonitrile, N,N-dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran, were selected for comparison. 10mL of reaction stock solution was added to five centrifuge tubes, and the above-mentioned several organic reagents were added, and the tubes were shaken thoroughly and left to stand for 30min. As can be seen from the comparison results, the acetonitrile group has obvious layer separation phenomenon compared with other organic reagents. The ethanol group used in the traditional purification method does not undergo centrifugation and cannot separate the carbon quantum dots, so acetonitrile was selected as the organic reagent in the purification process of water-soluble carbon quantum dots. Figure 15 is a photograph showing the layer separation situation when different solvents are selected.

[0063] The above content is only a preferred embodiment of the present invention, and does not limit other aspects of the present invention, and those skilled in the art can use the technical content disclosed above to modify or reshape the equivalent embodiment of the same modification. Without departing from the content of the solution of the present invention, simple modifications, equivalent modifications and reshaping made to the above embodiment based on the technical essence of the present invention shall all fall within the protection scope of the present invention.

Claims

1. Step 1: dissolving a soluble carbon-containing organic substance in ultrapure water, so that the mass ratio of carbon element in the soluble carbon-containing organic substance to water is 1:10,000 to 1:100; Step 2: Filling the pressure reactor with reaction liquid until it is full and sealing the reactor; Step 3: Start the heating program to rapidly increase the temperature to 380° C. and maintain the pressure in the reactor at 23 MPa or higher; Step 4: Activating the cooling system to cool the reactants in the reactor; Step 5: After cooling, collecting and quantifying the resulting aqueous solution of carbon quantum dots; Step 6: Separating and purifying the aqueous solution of carbon quantum dots.

2. 2. The method for preparing high purity carbon quantum dots according to claim 1, characterized in that after step 1, a soluble dopant material is added to the solution and completely dissolved, the soluble dopant material comprises nitrogen, phosphorus or sulfur element, and the ratio of the dopant element and the carbon source in the soluble dopant material is less than or equal to 1:

1.

3. 2. The method for preparing high purity carbon quantum dots as claimed in claim 1, wherein the soluble dopant material is dimethylsulfoxide.

4. The method for preparing high purity carbon quantum dots as claimed in claim 1, characterized in that in step 3, the reaction time is 10-15 minutes.

5. 2. The method for preparing high-purity carbon quantum dots according to claim 1, wherein the soluble carbon-containing organic matter is an organic acid or a sugar, or an organic acid and a sugar.

6. The method for preparing high purity carbon quantum dots according to any one of claims 1 to 5, characterized in that in step 4, the reactants in the reactor are cooled to room temperature within 15 minutes.

7. The method for preparing high purity carbon quantum dots as claimed in claim 6, characterized in that in step 4, the temperature of the reactor is lowered using glycol coolant at -5°C.

8. Step 6 includes: 6.1: Add acetonitrile to the solution and shake to mix thoroughly; 6.2: Allowing the mixed solution to stand in the dispenser for 30 minutes; 6.3: Collecting the bottom layer of the black viscous liquid and drying it to remove traces of residual acetonitrile to obtain a pure product of carbon quantum dots.

9. 9. The method for preparing high purity carbon quantum dots according to claim 8, characterized in that in step 6.3, after collecting the lower layer black viscous liquid, add acetonitrile to the black viscous liquid in a ratio of 1:1, shake to mix thoroughly, separate into layers, and then dispense again. Repeat the above steps 5 times until the volume of the lower layer black viscous liquid remains unchanged, collect the black viscous liquid, and dry to remove traces of residual acetonitrile, to obtain a pure product of carbon quantum dots.

10. A high-purity carbon quantum dot material, characterized in that it is prepared by the carbon quantum dot preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing high purity carbon quantum dots by using microwave method

    CN103588193A

  • Preparation method and application of carbon dots from beer

    CN105727313A

  • Carbon material for formaldehyde purification and preparation method thereof

    CN114749149A

  • Oil-soluble carbon quantum dots, nanofluid composition containing oil-soluble carbon quantum dots and method for inhibiting carbon dioxide flooding asphaltene deposition

    CN114751398A

  • Production method of luminescent nanocarbon

    JP2017043539A